Empowering Malian women living with HIV regarding serostatus disclosure management: Short-term effects of a community-based intervention. Issue 2 (February 2018) - Bernier, Adeline; Yattassaye, Adam; Beaulieu-Prévost, Dominic; Otis, Joanne; Henry, Emilie; Flores-Aranda, Jorge; Massie, Lyne; Préau, Marie; Keita, Bintou Dembélé
Highlights: Gundo-So: an empowerment program from Malian WLHIV regarding serostatus disclosure. The short-term effects of the program were evaluated using a pre-post study. Six (in)direct indicators were measured, including psychological and physical health. A statistically significant change was observed for all six outcomes. Strong need for programs encouraging free and informed decisions regarding disclosure. Abstract: Objective: The objective of this study was to assess the short-term effects of Gundo-So—a program aimed at empowering Malian women living with HIV (WLHIV) regarding serostatus disclosure management. Methods: A pre-experimental study with two measures (one week before and four weeks after Gundo-So) was carried out. A 35-item questionnaire was administered to a convenience sample of 210 WLHIV. Six outcomes were considered: ability to decide whether or not to disclose HIV status, self-efficacy to keep HIV status a secret, self-efficacy to disclose HIV status, feeling crushed by the weight of secrecy, perceived physical health, and perceived psychological health. For each outcome, temporal changes associated with the intervention were assessed using linear regressions with random intercepts. Results: Statistically significant change was observed for all six outcomes between the pre- and post-intervention measures. Furthermore, several variables were associated with the baseline levels of the outcomes and the intervention effect. Conclusion: The results suggest that Gundo-So empowers Malian WLHIV with regard to serostatus disclosure management, thus improving their perceived physical and psychological health. Practical implications: These results highlight the need for programs to empower WLHIV regarding serostatus disclosure, so that WLHIV can make free and informed decisions regarding serostatus disclosure.